2013
DOI: 10.1002/adem.201300081
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for the Processing of Advanced Polymer Derived Ceramics with Carbon Nanotubes with the Help of Pores

Abstract: In a novel approach, a nickel‐doped carbon rich preceramic polymer is converted into a carbon nanotubes (CNT) bearing polymer derived ceramic (PDC). Milling and field‐assisted sintering demonstrate that the CNTs remained stable during processing, and the CNTs are found to be embedded in the PDC matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Furthermore, CNTs were synthesized from a borazine-based precursor including nickel catalyst 5 [24] andYa-Li Li reported the fabrication of SiOC-CNTs composite by a one-step process via the in situ growth of CNTs during the pyrolysis of a preceramic polymer (polysiloxane) including FeCl 3 as catalyst [25]. Recently, Mantzel et al [26] took one step further to not only in situ form CNTs in pyrolyzed Si-O-C samples but also sinter/densify the ceramic body by field assisted sintering technology, and their results showed that CNTs could survive the harsh sintering conditions and significantly improve the mechanical properties, e.g., hardness, for the samples sintered at 1050ºC when compared with CNT-free ones.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CNTs were synthesized from a borazine-based precursor including nickel catalyst 5 [24] andYa-Li Li reported the fabrication of SiOC-CNTs composite by a one-step process via the in situ growth of CNTs during the pyrolysis of a preceramic polymer (polysiloxane) including FeCl 3 as catalyst [25]. Recently, Mantzel et al [26] took one step further to not only in situ form CNTs in pyrolyzed Si-O-C samples but also sinter/densify the ceramic body by field assisted sintering technology, and their results showed that CNTs could survive the harsh sintering conditions and significantly improve the mechanical properties, e.g., hardness, for the samples sintered at 1050ºC when compared with CNT-free ones.…”
Section: Introductionmentioning
confidence: 99%
“…These tentative hypotheses have been deduced from previous studies of Ni/Co-containing PDC materials. 15,16,50,51 It is believed that further studies are necessary to explain the role of Overall, the surface morphology analysis confirms that with the existence of pores in PDC the addition of Ni and Co was beneficial for an in situ growth of CNTs. Moreover, the thermal stability of the metal-containing ceramics is slightly better than that of bare H.A as a result of in situ grown CNT, which improves the overall thermal stability of the ceramic composite (Figure S4).…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…It is already reported that in catalystassisted pyrolysis the in situ growth of CNT is possible in porous PDC, with the help of a metal catalyst. 15,16,43,49 The S7). However, in the case of bare H.A, the formation of CNTs at both temperatures cannot be observed (Figure 2a,b, Figure S7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystallization of both phases increase with temperature. Mantzel et al 28) found that above 1000°C the metastable matrix of SiOC transforms to stable SiO 2 and SiC, which was detected within their XRD spectra. XRD spectra of the SiOC/MoSi 2 composites after annealing at high temperatures are depicted in Fig.…”
Section: Ageing At Elevated Temperatures and Electrical Resistivitymentioning
confidence: 91%